DESCRIPTION OF MOTHER’S SELF EFFICACY IN COMPLEMENTARY FEEDING AND STUNTING AMONG CHILDREN - Nugraheni Dwi Pratiwi Putri; Veni Hadju; Rahayu Indriasari; Healthy Hidayanty; Marini Amalia Mansur (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Introduction: Stunting is a chronic malnutrition problem caused by lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is shorter than the standard age. Mother's self-efficacy in offering MP-ASI is a mother's self-confidence in carrying out the feeding process which includes the quantity and quality of MP-ASI, safety in providing food and the responsive feeding. Objective: To describe the mother's self-efficacy in giving complementary feeding and the incidence of stunting in children aged 6-23 months. Methods: This study used a descriptive design. Involving 100 samples of baduta and mothers, obtained by cluster random sampling technique. Data was collected by using a complementary feeding self efficacy (CFSE) questionnaire and measuring baduta’s body length using a lengthboard. This research was conducted on Barrang Lompo Island, Makassar City. Descriptive data analysis using SPSS 25 application. Result: Mother's self-efficacy in the high category is 52% and low 48%. Majority of mother's self-efficacy in giving complementary feeding tends to be low in the quality and quantity aspects of MP-ASI is 55% and the responsive feeding aspect is 52%. The incidence of stunting reached 31% of the total sample. Conclusion: There are still many mother's self-efficacy in the low category, especially in the quality and quantity of MP-ASI aspects and responsive feeding aspects. The incidence of stunting is 31%. Mentoring are needed for mothers whose self-efficacy is still low and increased knowledge of mothers through nutrition education, especially about stunting and providing good complementary feeding. Keywords: Stunting, Mother's self-efficacy, Complementary Feeding, Baduta